A study on the safety of animal shipment in MASkargo / Mohammad Fairuz Abdul Rahman - Abdul Rahman, Mohammad Fairuz (Faculty of Business and Management, 2009)
MASkargo is a leading cargo industry in Malaysia and currently it has about 709 employees worldwide. MASkargo has numbers of stations worldwide and therefore it is important to ensure that all the worldwide staffs are satisfied with the company and benefits given to them. A study was carried out to identify the factors that give an impact to the safety of animal shipment here in MASkargo. Besides that, this study will also reveal the benefits offered by MASkargo to their customers. A set of questionnaire concerning the factors regarding to safety of animal has been distributed to the customers of MASkargo Animal Hotel. A number of 32 respondents have been selected randomly to answer the questionnaire. This study has revealed the factors of container packaging requirement, ventilation system and operation of animal handling by ground and air handling that ensuring the safety of animal shipment. From the study, majority of the respondents are satisfied with MASkargo Animal Hotel services and agreed on Operation handling and container packaging is the most influenced factors. Besides that, there are some additional information and suggestion that given by the respondent regarding to the safety of animal shipment in MASkargo.